Exogenous TNFR2 activation protects from acute GvHD via host T reg cell expansion - Chopra, Martin; Biehl, Marlene; Steinfatt, Tim; Brandl, Andreas; Kums, Juliane; Amich, Jorge; Vaeth, Martin; Kuen, Janina; Holtappels, Rafaela; Podlech, Juergen; Mottok, Anja; Kraus, Sabrina; et al. (Journal of Experimental Medicine, 2016)
Donor CD4(+)Foxp3(+) regulatory T cells (T reg cells) suppress graft-versus-host disease (GvHD) after allogeneic hematopoietic stem cell transplantation (HCT [allo-HCT]). Current clinical study protocols rely on the ex vivo expansion of donor T reg cells and their infusion in high numbers. In this study, we present a novel strategy for inhibiting GvHD that is based on the in vivo expansion of recipient T reg cells before allo-HCT, exploiting the crucial role of tumor necrosis factor receptor 2 (TNFR2) in T reg cell biology. Expanding radiation-resistant host T reg cells in recipient mice using a mouse TNFR2-selective agonist before allo-HCT significantly prolonged survival and reduced GvHD severity in a TNFR2- and T reg cell-dependent manner. The beneficial effects of transplanted T cells against leukemia cells and infectious pathogens remained unaffected. A corresponding human TNFR2-specific agonist expanded human T reg cells in vitro. These observations indicate the potential of our strategy to protect allo-HCT patients from acute GvHD by expanding T reg cells via selective TNFR2 activation in vivo.
EVALuna2:7721